Interaction effect of seaweed extract and inoculation on growth, nodulation and nutritional quality of two cowpea varieties (Vigna unguiculata L. Walp) - Makoro, MacDonald (My University, 2015)
Two studies (field and tunnel house experiments) were conducted during the 2012/2013 growing season to assess the effect of a commercial seaweed extract (Technikelp) and Bradyrhizobia inoculation on growth, nodulation, yield and nutritional quality of cowpea. The field experiment was laid out as a 3-way factorial arrangement, and fitted into a randomized complete block design (RCBD) with three factors: i) Two cowpea varieties (Brown landrace and Bechua na white), ii) Two Inoculation levels (with and without Bradyrhizobium inoculation) and iii) Three seaweed extract concentrations to water (1:100, 1:500 and no seaweed extract as the control). The treatments were combined and replicated four times. Cowpea seeds were sown at an intra-row spacing of 20 cm and inter- row spacing of 60 cm with a plot size of 3 m x 3.6 m (10.8 m2) with each plot having six rows and a plant population of 96 plants per plot. Six litres (6000 ml) of each of the diluted seaweed extract levels was applied per plot as root drench at planting, 14 and 28 days after planting (DAP). The seaweed extract was applied immediately after irrigation. The tunnel house experiment was also laid out as a 3-way factorial experiment and fitted into a randomized complete block design (RCBD) with three factors: i) Two cowpea varieties (Brown cowpea landrace and commercial variety; Bechuana white), ii) Two Inoculation levels (with and without Bradyrhizobium inoculation) and iii) Three seaweed extract concentrations to water (1:100, 1:500 and no seaweed extract as the control). The factors were combined and replicated four times. Nine litre (9 L) nursery bags with a dimension of 175 x 150 x 350 mm were filled with 5 kg of sandy loam Hutton soil obtained from the University of Limpopo experimental farm. Analysis of variance revealed that the variation in genetic composition dictated the growth and yield performance of the two cowpea varieties. The current study revealed that all three factors had a significant effect of growth, nodulation, yield as well as the uptake of several mineral nutrients. The results showed that the Brown landrace took longer to reach flowering (60.45 days) and physiological maturity (142.02 days) compared to Bechuana white variety which took 57.18 days to reach 50% flower and 121.11 days to reach physiological maturity. In both the field and tunnel house experiments, the application of 1:100 v/v seaweed extract resulted in a 81-88% increase in the number of effective nodules when compared to the control. Variety, seaweed extract and inoculation had a significant (p≤ 0.05) effect on grain yield. The Bechuana white variety recorded grain yield of 1915 kg ha-1 compared to the 1021 kg ha-1 by the Brown landrace variety. The application of 1:500 v/v seaweed extract increased grain yield by 9.5% while the application of 1:100 v/v resulted in a 29.9% increase. The application of Bradyrhizobia inoculation increased grain yield by up to 40% when compared to the uninoculated treatment. In both the field and tunnel-house experiments, correlation analysis revealed a positive relationship between chlorophyll content and number of effective nodules per plant. In the tunnel house experiment, correlation analysis gave an R2 value of 0.80 while an R2 value of 0.70 was recorded in the field experiment, indicating a strong relationship between chlorophyll content and nodulation. Furthermore, a positive relationship was also observed between nodulation and pod formation with an R2 value of 0.69. Correlation analysis also revealed a positive relationship between pod formation and grain yield with a R2 value of 0.62. Statistical analysis revealed a significant variety x inoculation effect on the number of days to 50% flowering, as well as the yield components and seed nutritional quality. The application of seaweed extract in the presence of inoculation improved nodulation and chlorophyll content, yield components, as well as leaf and grain nutritional quality. Response of variety to seaweed extract was observed on shelling percentage, as well as leaf K and Fe content, and seed B content. The combination of seaweed extract x inoculation x variety had a significant effect on the number of pods per plant, grain yield, shelling percentage as well as harvest index. Economic analysis revealed that the application of both inoculation and seaweed extract are highly profitable. The application of inoculation resulted into greater profit of R32818/ha relative to uninoculated treatments while the application of 1:100 v/v seaweed extract concentration resulted into greater profitability of R32191/ha and ultimately resulted into higher returns to investment in the technology. Overall, the results from this study suggest that the adoption of application of inoculants and seaweed extract will not only improve yield and nutrition of cowpea, but has the potential to improve the livelihoods of small scale farmers due to their high marginal returns.
Thesis (M.Sc. Agriculture (Agronomy)) -- University of Limpopo, 2015
Keywords: Seaweed extract; Bradyrhizobia inoculation; Cowpea variety; Legumes -- Inoculation; Cowpea; Seaweed; Marine algae as food